FENOMENA PILGUB BABEL 2017 (MEMAHAMI KARAKTER PEMILIH PEMULA DALAM MENENTUKAN HAK KONSTITUSIONALNYA - Rio Armanda Agustian; Abdul Rasyid Saliman (PROGRESIF: Jurnal Hukum, 2017)
This study discusses the phenomenon of Babel Pilgub 2017 in understanding the extent of the character of early voters in determining their constitutional rights in the Pilgub. The novice viewers' views are now evolving and have undergone many changes. The approach model used by the beginner Bangka Beliutng voters in determining and dropping their choice. The advance level of the beginner's education of Bangka Belitung became the main reason for the occurrence of electoral disorientation. So far, the most dominant and decisive primordial factor of primal voters has shifted toward the achievement factor of the candidates. This can be seen from 27,988 novice voters or 3.08% of the total number of existing voters list, the distribution of candidate achievement relationships with the choice of the novice to the spouse is very strong. The results of this study indicate that there is a tendency to change the character of the beginner voters before they decide and choose their choice to cover five aspects such as the novice voters to choose candidate pairs of governors / representatives who are faithful, honest, rich, fair and able to separate between the people's property and private property, knowing what the advantages and disadvantages of the candidates are, they do not choose candidate pairs who use money politics or any unlawful means to get people to vote for them, and they choose candidate pairs that use the wealth of the people for the importance of education and welfare.